Model the effectiveness of a systematic process of technical re-equipment of production - Дар’я Валеріївна Безугла (Tehnologìčnij Audit ta Rezervi Virobnictva, 2015)
In the article the modern definition of "technical re-equipment of production", outlines the methodological approach to the analysis of its nature and content, as a system process efficiency is determined by performing technical-technological, organizational-economic and innovation-implementing subsystems consisting of technical object retooling.